The Facsimile edition of the Nag Hammadi Codices : Cartonnage (Biblical Studies, Ancient Near East and Early Christianity - Book Archive pre-2000., 1979)
Published under the Auspices of the Department of Antiquities of the Arab Republic of Egypt in Conjunction with the United Nations Educational, Scientific, and Cultural Organization. The collection of thirteen codices found in upper Egypt near Nag Hammadi in 1946 is one of the major archaeological discoveries of our time. Apparently the library of a Gnostic community in late antiquity, the codices are a repository of important spiritual materials from throughout the ancient world. Hence a thorough analysis of this new material is indispensable for any proper understanding of the history of religions in this period. The rich documentation which the codices add to early Coptic text material promises to raise to a new precision the historical analysis of that language. This edition presents collotype reproductions in natural size of all folios of the thirteen codices as well as reproductions of the covers and photographs previously taken of fragments that are now lost.